Accuracy of a cut-off value based on the third molar index: Validation in an Australian population. (September 2016) - Franklin, Daniel; Karkhanis, Shalmira; Flavel, Ambika; Collini, Federica; DeLuca, Stefano; Cameriere, Roberto
Highlights: I 3M has a high level of sensitivity and specificity in an Australian population. Population specific age standards should be applied where possible. Further studies needed to test accuracy of I 3M with other legal age indicators. Abstract: According to Recommendation N°196 of the Australian Law Reform Commission (ALRC), the age at which a child reaches adulthood for the purposes of criminal law should be 18 years in all Australian jurisdictions. With specific reference to age at majority, the only tooth with development spanning adolescence (and thus the legally relevant 18 years of age) is the third molar, which limits the number of methods that can be applied from those available in the published literature. The aim of the present study is to test the accuracy of the third molar index ( I 3M  = 0.08), based on the correlation between chronological age and normalized measures of the open apices and height of the third mandibular molar, in order to assess the legal adult age of 18 years. Digital orthopantomographs of 143 living Australian subjects (72 boys and 71 girls) are analyzed. The results demonstrate that the sensitivity is 0.90 in boys and 0.90 in girls; associated specificity values are 0.85 and 0.87 respectively. We conclude that the cut-off value of I 3M  = 0.08 is statistically robust and thus valid for forensic application in an Australian population.